Maturity Indices and Harvesting Practice of Arumanis' Mango Related to The Target Market - Tridjaja, N. O.; Mahendra, M. S. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2000)
Mango as a climacteric fruit is frequently harvested when less than fully ripe. This isoften necessary to obtain optimal eating quality at the time of consumption where marketsare a considerable distance from the place of harvest. In this study the age of fruit was calculated, based on the time of flowering. Theorchard selected for the trials was located in northern part of Bali, Indonesia. Thelaboratory analyses were carried out at Udayana University. The results showed that optimal maturity of 'Arumanis' mango for best consumptionis when the fruit is harvested 13-14 weeks after flowering. Fruit age has a closerelationship with total soluble solids (TSS), total acidity and pH content. This studyfound that'Arumanis'mango is best for consumption when the TSS content of the fruit isnot less than 16.8'Brix, total acidity 0. 18%, pH 4.8, flesh colour rating 6-6.5, and tastescore 5.Keyword: mango, maturity